GLOBAL COLLABORATION: REVOLUTIONIZING INTERNATIONAL COMMERCE AND EXPANDING THE ENTREPRENEURIAL POTENTIALS OF YOUNG ENTREPRENEURS - Juniarty, Juniarty; Tan, Jacob D.; Wijayanti, Cynthia A. (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
In today's globalized and digitally connected world, cross-border collaboration is a key enabler of innovation, trade, and entrepreneurship. This community service activity conducted by the Universitas Pelita Harapan Business School aimed to equip students from Iloilo University, Philippines, with the insights and mindset required to thrive in international business. The seminar titled Global Collaboration: Revolutionizing International Commerce and Expanding the Entrepreneurial Potentials of Young Entrepreneurs highlighted cross-cultural partnerships, digital technologies, and international market access as critical enablers of entrepreneurial opportunities. Practical strategies for building global networks, innovating through e-commerce, and leveraging digital tools were discussed. The program empowered students to think globally, act strategically, and foster sustainable innovation.